The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1586/egh.11.105
|View full text |Cite
|
Sign up to set email alerts
|

Role of the multidisciplinary team in the diagnosis and treatment of hepatocellular carcinoma

Abstract: It has long been appreciated that hepatocellular carcinoma (HCC) is a complex disease. HCC is typically preceded by liver cirrhosis, which is itself caused by various types of hepatitis of both viral and nonviral etiologies. Thus, the treatment of patients with HCC requires multiple healthcare professionals, including hepatologists, medical oncologists, surgical oncologists, transplantation surgeons, diagnostic radiologists, pathologists, nurses, nurse practitioners and interventional radiologists. These speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 76 publications
0
46
0
Order By: Relevance
“…The increased proportion of patients completing guidelinedriven MDE observed among those evaluated through the VTB program and the overall high rate of patients completing this standard (100%) are noteworthy-higher than those reported by other studies 12,22 -and reflect the magnitude of the impact on cancer care derived from an organized VTB regional program. A retrospective cohort study using the VA Hepatitis C Clinical Case Registry in 2013 reported that only 31% of patients with HCC were evaluated by a surgeon or oncologist 7 ; another analysis using the SEER-Medicare database over a similar time period revealed that only 39% of patients with HCC were evaluated by Ն three HCC cancer care specialists.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The increased proportion of patients completing guidelinedriven MDE observed among those evaluated through the VTB program and the overall high rate of patients completing this standard (100%) are noteworthy-higher than those reported by other studies 12,22 -and reflect the magnitude of the impact on cancer care derived from an organized VTB regional program. A retrospective cohort study using the VA Hepatitis C Clinical Case Registry in 2013 reported that only 31% of patients with HCC were evaluated by a surgeon or oncologist 7 ; another analysis using the SEER-Medicare database over a similar time period revealed that only 39% of patients with HCC were evaluated by Ն three HCC cancer care specialists.…”
Section: Discussionmentioning
confidence: 64%
“…Tumor boards (TBs) have emerged as a multidisciplinary forum targeted at providing this standard 4,8 and have been shown to be associated with improved satisfaction, outcome, and survival of patients with HCC. [9][10][11][12][13] Effective multidisciplinary evaluation (MDE) through a TB is dependent on local infrastructure and oncology workforce, which are not available at every institution.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of exactly which features of HCC and patient health may predict the clinical outcome of combination regimens is essential for prescribing individualized evidence-based therapeutic strategies. 40 …”
Section: Synergies and Combination Strategiesmentioning
confidence: 99%
“…That is why it is considered that tumour behavior can be described using alterations of the p53 gene, and these are also considered an independent factor in natural disease evolution prognosis [17].…”
Section: Discussionmentioning
confidence: 99%